2021
DOI: 10.1371/journal.pone.0251235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms as prognostic factors for recurrent kidney stones: A systematic review and meta-analysis

Abstract: Genetic polymorphisms have been suggested as risk factors affecting the occurrence and recurrence of kidney stones, although findings regarding the latter remain inconclusive. We performed this systematic review and meta-analysis to clarify the associations between genetic polymorphisms and recurrent kidney stones. PubMed, SCOPUS, EMBASE, and Cochrane Library databases were searched through May 28th, 2020 to identify eligible studies. The Quality in prognostic studies (QUIPS) tool was used to evaluate bias ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…Understanding the relevant genetic factors may pave the way towards personalized approaches to assessing the risk of nephrolithiasis in individuals with sarcoidosis, and probably also in individuals with other diseases, allowing for targeted preventive strategies and more-effective management of renal complications [17,29]. Renal calculi appear to be a marker of chronicity, with long-term corticosteroid therapy required in most cases [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the relevant genetic factors may pave the way towards personalized approaches to assessing the risk of nephrolithiasis in individuals with sarcoidosis, and probably also in individuals with other diseases, allowing for targeted preventive strategies and more-effective management of renal complications [17,29]. Renal calculi appear to be a marker of chronicity, with long-term corticosteroid therapy required in most cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the role of vitamin K2 in local γ-carboxylation, it would be interesting to understand the vitamin K2 statuses of stone formers [15]. Genetic polymorphisms have been proposed to be risk factors affecting the occurrence and recurrence of kidney stones [17]. Previously, it was shown that the expression of the VKORC1 protein is decreased in renal tissues of patients with CaOx urolithiasis, indicating that VKORC1 may play an important role in the formation of CaOx stones [18].…”
Section: Introductionmentioning
confidence: 99%
“…В частности, однонуклеотидные полиморфизмы (англ. -Single Nucleotide Polymorphism, SNP) в различных генах могут оказывать влияние на риск развития и рецидива данного заболевания [7]. Раннее установление наследственной предрасположенности к манифестации и рецидиву данного заболевания может оказаться важнейшим звеном в профилактике мочекаменной болезни [8].…”
Section: Introductionunclassified